2016
DOI: 10.1021/acs.biomac.5b01335
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Charge-Converted Monoclonal Antibodies by Combinatorial Design of Block/Homo Polyion Complex Micelles

Abstract: Direct intracellular delivery of antibodies has gained much attention, although only a few agents have been developed, and none of them has reached clinical stages. The main obstacles here are the insufficient characteristics of delivery systems including stability and appropriate ability for intracellular antibody release. We tailored the structure of polyion complex (PIC) micelles by loading transiently charge-converted antibody derivatives for achieving enhanced stability, delivery to cytosol, and precise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 19 publications
0
94
0
1
Order By: Relevance
“…Although endosomal trapping has been a major challenge for intracellular functional delivery of RNA, peptides, and antibodies, our confocal microscopic studies with the PS DNA oligo-modified tubulin antibodies show that the delivered antibodies coincide with the tubulin structure. The majority of the current antibody intracellular delivery methodologies are unidirectional (11)(12)(13)(14)(15)(16)(17)(18)(19). This study shows that cellular retention of our modified antibodies requires the presence of a target antigen because the modified nontargeting antibodies, within a relatively short time, become absent in cultured living cells and in treated tumors.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although endosomal trapping has been a major challenge for intracellular functional delivery of RNA, peptides, and antibodies, our confocal microscopic studies with the PS DNA oligo-modified tubulin antibodies show that the delivered antibodies coincide with the tubulin structure. The majority of the current antibody intracellular delivery methodologies are unidirectional (11)(12)(13)(14)(15)(16)(17)(18)(19). This study shows that cellular retention of our modified antibodies requires the presence of a target antigen because the modified nontargeting antibodies, within a relatively short time, become absent in cultured living cells and in treated tumors.…”
Section: Discussionmentioning
confidence: 79%
“…It is therefore highly desirable to efficiently deliver antibodies intracellularly, to make challenging targets amenable to therapy. Over the years, multiple studies, primarily in cultured cells, have shown the feasibility of facilitating antibodies' cellular internalization (11)(12)(13). Furthermore, a number of studies have shown the potential of therapeutic benefits in vivo of a nuclear-penetrating lupus anti-DNA autoantibody (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…4). Previously reported cationic blocks to interact with anionic proteins includes poly(L-lysine) (P(Lys), [25] poly(aminoalkyl aspartamide), [26] and poly(aminoalkyl methacrylate) (PAMA). [27] For anionic proteins, poly(acrylic acid) (PAA) and poly(aspartate) (P(Asp)) [28] can be used as the ionic block for PIC micelle formation.…”
Section: Binding Proteins Using Charged Polymersmentioning
confidence: 99%
“…The advantage of this technique is not only the quick introduction of excess negatively charged groups on the surface of the antibody, but also the quick cleavage of this amide bond at low pH, restoring the full activity of the antibody. [26] Co-Encapsulation of Charged Polymers Addition of homopolymers that carry a similar charge to the payload can help stabilise the micelle against disassembly in an environment of high ionic strength. A study that used entrapment of different ratios of positive charged lysozyme and poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA) Fig.…”
Section: Supercharging Of Proteinsmentioning
confidence: 99%
“…The facile preparation process of biomolecular assembly is attractive in terms of pharmaceutical and food‐industrial applications for full utilization of their function without denaturation . Recently, block‐copolymer‐based submicrometer‐scaled (subμ‐) PIC structures have been rationally designed for biomedical applications to enhance the bioavailability and controlled release of proteins and nucleic acids . We very recently reported block‐copolymer‐based PIC vesicles (PICsomes) of ≈100 nm diameter, which allow for direct encapsulation of enzymes into their inner cavity, and demonstrated that chemically crosslinked PICsomes can deliver enzymes efficiently to target tumor tissues without their deactivation .…”
Section: Introductionmentioning
confidence: 99%